THE MEANING OF “DENGKA SE LOLO” HARVEST PARTY FOR THE PEOPLE IN PABENTENGANG VILLAGE, KAEMBA HAMLET (Karya Ilmiah Mahasiswa (KIMA), 2024)
The purpose of this study is to describe the process of carrying out the rice harvest festival "Dengka Se Lolo" and find out the meaning of the rice harvest festival "Dengka Se Lolo" in Pabentegang Village, Dusun Kaemba. This study uses qualitative data processing with data collection techniques through observation, interviews and documentation. Data analysis techniques using reduction techniques, data display and depiction of hell. The data from this study is the culture of the Bugis Harvest Festival which is a hereditary tradition passed down from the ancestors. The Harvest Festival is held as an expression of the community's gratitude to the Creator and to strengthen ties between local communities. The results of this study indicate that the rice harvest festival "Dengka Se lolo" is one of the traditions and culture of the people of Kaemba Village which is routinely held after the main harvest, namely Dengka sel lolo or rice mill. Crush the rice with a pestle and mortar. Researchers also found that this harvest festival is routinely held every year because it upholds ancestral traditions and shows gratitude for an abundant harvest.